Pengaruh Komposisi Campuran dan Ukuran Butiran terhadap Kualitas Briket Arang dari Limbah Serbuk Kayu Mahoni (Swietenia macrophylla) dengan Perekat Daun Jarak Pagar (Jatropha curcas) - Prasetyo, Dafit Ari; Violita, Elvira Anne; Sholikah, Umi; Astuti, Ulvi Pri (P3M Politeknik Negeri Jember, 2025)
Mahogany sawdust waste (Swietenia macrophylla) has not been widely utilized and is only used as baglog in oyster mushroom cultivation and particle board mixture. The potential of mahogany sawdust waste as fuel is quite high, especially when viewed from its calorific value which reaches 4,652.34-4,844.83 cal/g. Making mahogany sawdust into charcoal briquettes with a mixture of castor oil plant leaves (Jatropha curcas) can increase the calorific value and its usefulness as fuel. The variations of the castor oil leaf adhesive mixture used are 10%, 20%, and 30% as well as variations in the size of mahogany sawdust charcoal grains 35 mesh, 60 mesh, and 100 mesh. The briquette with the best composition produced is variation A1B1, namely a briquette with a 10% adhesive mixture and a particle size of 35 mesh (particle size ≃ 0.5 mm) with a calorific value of 6,122 cal/g, water content of 5.62%, ash content of 6.46% and has met the quality standards for charcoal briquettes according to SNI 1-6235-2000